Beige Fat Maintenance; Toward a Sustained Metabolic Health - Rabiee, Atefeh (Frontiers in Endocrinology, 2020)
Understanding the mammalian energy balance can pave the way for future therapeutics that enhance energy expenditure as an anti-obesity and anti-diabetic strategy. Several studies showed that brown adipose tissue activity increases daily energy expenditure. However, the size and activity of brown adipose tissue is reduced in individuals with obesity and type two diabetes. Humans have an abundance of functionally similar beige adipocytes that have the potential to contribute to increased energy expenditure. This makes beige adipocytes a promising target for metabolic disease therapies. While brown adipocytes tend to be stable, beige adipocytes have a high level of plasticity that allows for the rapid and dynamic induction of thermogenesis by external stimuli such as low environmental temperatures. This means that after browning stimuli have been withdrawn beige adipocytes quickly transition back to their white adipose state. The detailed molecular mechanisms regulating beige adipocytes development, function, and reversibility are not fully understood. The goal of this review is to give a comprehensive overview of beige fat development and origins, along with the transcriptional and epigenetic programs that lead to beige fat formation, and subsequent thermogenesis in humans. An improved understanding of the molecular pathways of beige adipocyte plasticity will enable us to selectively manipulate beige cells to induce and maintain their thermogenic output thus improving the whole-body energy homeostasis.